Clinical characteristics, therapeutics, and treatment outcomes of adult patients with anti-melanoma differentiation-associated gene 5 dermatomyositis: A single-center experience from South India - Shivraj Padiyar; Aswin M Nair; Bijesh Yadav; Prathyusha Manikuppam; Jha Avanish; Abhilasha Arvind Manwatkar; John Mathew (Indian Journal of Rheumatology)
Introduction: To study the clinical characteristics and treatment outcomes of patients with anti-melanoma differentiation-associated gene 5 (MDA5) dermatomyositis (DM). Methods: This was a retrospective study done between 2019 and 2021 in a tertiary care center in South India. All consecutive patients, presenting to the adult rheumatology department, classified as idiopathic inflammatory myositis (IIM), and positive for anti-MDA5 antibodies, were included in the study. Baseline characteristics of anti-MDA5 patients were compared with the data of non-MDA5 patients over the last 10 years. Clinical, biochemical, and treatment responses were assessed on follow-up. Complete and partial responders were identified using predefined criteria. Factors predicting mortality were determined by logistic regression analysis. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. Results: A total of 29 adult patients of IIM were positive for anti-MDA5 antibody during the study period. The mean (±standard deviation) age of the patients was 40.3 (±13.02) years with a female:male ratio of 1.4:1. Panniculitis, calcinosis, palmar papules, and ulcerated Gottron's were the specific cutaneous manifestations, seen in 3 (10%), 7 (24%), 4 (13.4%), and 7 (24%) patients, respectively. A total of 14 patients (48.1%) had clinically amyopathic DM and 17 patients (60.7%) had interstitial lung disease (ILD) diagnosed by high-resolution computerized tomography scan, of which organizing pneumonia was the predominant pattern. Complete response was seen in 10 patients (43.4%), while a partial response was seen in 8 patients (34.7%). Five patients died on follow-up, accounting for mortality of 21%. Age >50 years was significantly associated with mortality (P = 0.025). Gottron's sign (P < 0.001), panniculitis (P < 0.001), calcinosis (P < 0.001), cutaneous ulcerations (P < 0.001), inflammatory arthritis (P < 0.001), and ILD (P < 0.02) were present more commonly in the anti-MDA5 IIM group, whereas myopathy (P < 0.001), elevated creatine phosphokinase (P < 0.001), and lactate dehydrogenase (P < 0.001) were more frequently present in the non-anti-MDA5 IIM group (n = 421). Conclusions: Anti-MDA5 DM represents a distinct and unique subset of IIM with characteristic clinical manifestations. Elderly age is a poor prognostic factor of mortality.